A Study on Satisfaction Evaluation and Improvement Paths for ASEAN International Students in Guangxi, China (Contemporary Education and Teaching Research, 2025)
Based on survey data from 100 ASEAN students studying in Guangxi, this study applied a satisfaction evaluation model and conducted correlation and regression analyses to examine overall satisfaction and its influencing factors. The results show that the overall satisfaction level is relatively high, with an average score of 3.74 and a satisfaction rate of 62%. Four main factors influence the overall satisfaction of ASEAN students in Guangxi: study status, living conditions, school evaluation and academic expenses. In addition, significant differences exist among students at different academic levels, students pursuing higher degrees tend to report higher levels of satisfaction. The education and teaching departments should address common issues faced by ASEAN students in Guangxi by improving the quality of international student recruitment, enhancing service levels for international students, and organizing regional competitions, so as to effectively improve the satisfaction of ASEAN students studying in Guangxi.